2015
DOI: 10.3389/fpls.2015.00136
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification and phytoremediation of selenium in China

Abstract: Selenium (Se) is an essential trace element for humans and animals but at high concentrations, Se becomes toxic to organisms due to Se replacing sulfur in proteins. Selenium biofortification is an agricultural process that increases the accumulation of Se in crops, through plant breeding, genetic engineering, or use of Se fertilizers. Selenium phytoremediation is a green biotechnology to clean up Se-contaminated environments, primarily through phytoextraction and phytovolatilization. By integrating Se phytorem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 107 publications
3
128
0
3
Order By: Relevance
“…Selenium, an essential element for animals and humans, has also been found to be beneficial to plants (Ellis and Salt, 2003; Wu et al, 2015). However, Se often exerts a dual effect on plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium, an essential element for animals and humans, has also been found to be beneficial to plants (Ellis and Salt, 2003; Wu et al, 2015). However, Se often exerts a dual effect on plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element for humans and animals, and some findings suggest that Se may be a beneficial element, which plays a novel role in plant biology for innovative crop production (Trumble et al, 1998; Rayman, 2000; Terry et al, 2000; Ellis and Salt, 2003; Hartikainen, 2005; Pilon-Smits et al, 2009; Zhu et al, 2009; Bañuelos et al, 2011; Hatfield et al, 2014; Wu et al, 2015). Selenium at low concentrations exerts positive effects for plants such as promoting growth, increasing antioxidative capacity, improving yield and quality, and delaying ripening and senescence (Hartikainen et al, 2000; Xue et al, 2001; Turakainen et al, 2004; Broadley et al, 2010; Pukacka et al, 2011; Pezzarossa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Se-phytoremediation, as discussed before, occurs primarily via phytoextraction opening the possibilities of using Se-rich biomass harvested from phytoremediating plants as a sustainable replacement of green manures and other supplementary sources meant to yield Se-fortified agricultural products for biofortification (Wu et al 2015). However, the feasibility of improving such biofortification processes with microbial inoculation still needs to be explored (Surade Jong et al 2015).…”
Section: Challenges and Future Prospectsmentioning
confidence: 97%
“…Recently, it has only been speculated that the hyperaccumulator-associated microflora plays a significant role in the establishment of interaction between plants and soil (Sura-de Jong et al 2015;Wu et al 2015). Using cultivation-based techniques, it has been shown that two selenium (Se)-hyperaccumulators, namely Astragalus bisulcatus and Stanleya pinnata are capable of harboring well-structured endophytic bacterial populations in their natural Se-rich surroundings.…”
Section: Plant-endophyte Partnership In Phytoremediationmentioning
confidence: 99%
“…Thus, there are demands that the example of Finland should be followed and soil Se levels increased by the addition of selenium to fertilizers (Reilly 2006 ). It could be noticed that, the range between the benefi cial and harmful doses of Se is quite narrow; the minimal Se nutrition levels for animals is about 0.05-0.10 mg kg −1 dry forage feed, while the toxic exposure level is 2-5 mg kg −1 dry forage (Wu et al 2015 ). Yuan et al ( 2012 ) reported that, there are two well-known endemic diseases linked to soil Se defi ciency and low Se daily intake.…”
Section: Selenium: the New/old Essential Poisonmentioning
confidence: 99%